Preferences for Truth-Telling - Johannes Abeler; Daniele Nosenzo; Collin Raymond (Institute for the Study of Labor (IZA), 2016)
Private information is at the heart of many economic activities. For decades, economists have assumed that individuals are willing to misreport private information if this maximizes their material payoff. We combine data from 72 experimental studies in economics, psychology and sociology, and show that, in fact, people lie surprisingly little. We then formalize a wide range of potential explanations for the observed behavior, identify testable predictions that can distinguish between the models and conduct new experiments to do so. None of the most popular explanations suggested in the literature can explain the data. We show that only combining a preference for being honest with a preference for being seen as honest can organize the empirical evidence.
Keywords: D03; D82; H26; I13; J31; 330; private information; honesty; truth-telling; lying; meta study